Clinical Heterogeneity in the Severe Asthma Research Program - Moore, Wendy C.; Fitzpatrick, Anne M.; Li, Xingnan; Hastie, Annette T.; Li, Huashi; Meyers, Deborah A.; Bleecker, Eugene R. (Annals of the American Thoracic Society, 2013)
The National Heart, Lung, and Blood Institute has sponsored several asthma clinical networks, but the Severe Asthma Research Program (SARP) is unique, because it is not a clinical trials network, and it includes both adults and children. Investigators in SARP have comprehensively characterized 1,644 patients with asthma over the past 10 years, including 583 individuals with severe asthma and 300 children below the age of 18 years. The diversity in clinical characteristics, physiologic measures, and biomarkers in a large number of subjects across the ages provides an ideal cohort in which to investigate asthma heterogeneity. Using both biased and unbiased approaches, multiple asthma phenotypes have been described in SARP. These phenotypic analyses have improved our understanding of heterogeneity in asthma, and may provide a starting point to transform clinical practice through the evidence-based classification of disease severity. Although these new phenotypes strive to make order out of a heterogeneous group of patients, they are limited by that heterogeneity. There may be large groups of patients, especially those with milder asthma, that can be grouped into a clinical phenotype to guide therapy, but there will always be patients on the "edge" of a phenotype who will not fit into these groupings. In the SARP cluster analysis, subjects on the "edge" of a phenotype frequently had lung function that was better or worse than other subjects in the same cluster, despite similar clinical characteristics. This suggests that different pathophysiologic mechanisms may be responsible for decrements in lung function in some subjects. This is extremely important for subjects with severe asthma who may be on the "edge" of two phenotypes that may be driven by different pathobiologic mechanisms that warrant different therapeutic approaches.